Immunisation schedule of the Spanish Association of Pediatrics: 2024 recommendations - Francisco José Álvarez García; Antonio Iofrío de Arce; Javier Álvarez Aldeán; María Garcés-Sánchez; Elisa Garrote Llanos; Abián Montesdeoca Melián; Marisa Navarro Gómez; Valentín Pineda Solas; Irene Rivero Calle; Jesús Ruiz-Contreras; Pepe Serrano Marchuet (Elsevier, 2024)
The AEP Immunization Calendar for 2024, with its immunization recommendations for pregnant women, children and adolescents residing in Spain, marks the 25th edition since the first one was introduced in 1995, being annual since 2003, as a vaccination calendar, and since 2023 as immunization schedule due to the inclusion of a monoclonal antibody for the prevention of RSV disease. Novelties for this year include the following: • Tables of systematic immunizations for healthy people and those belonging to risk groups. • Although vaccination recommendations were previously made for pregnant women, they have been now included in the table and a specific section has been created. • Vaccination against pneumococcus is recommended with one of the new expanded valence conjugate vaccines, replacing PCV13. • It is recommended to replace the meningococcus C vaccine at 4 months of age with the MenACWY vaccine, thus leaving the recommended schedule as 1 + 1 + 1 (4 months, 12 months and 12 years, with a catch-up for adolescents up to 18 years). • The intranasal flu vaccine is recommended as the preferred vaccine for people over 2 years of age. • Following the proposals of the WHO, ECDC and CISNS, vaccination against SARS-CoV-2 is now recommended only for people over 6 months of age with risk factors, using vaccines containing the XBB.1 lineage. Vaccination recommendations against covid in pediatrics will be updated periodically on the CAV-AEP website.The rest of the recommendations from the previous calendar remain unchanged. Resumen: El Calendario de Inmunizaciones de la AEP para 2024, con sus recomendaciones de inmunización para embarazadas, niños y adolescentes residentes en España, hace el número 25 desde el primero presentado en 1995, siendo anual desde 2003, como calendario de vacunaciones, y desde 2023 como calendario de inmunizaciones por la inclusión de un anticuerpo monoclonal para la prevención de la enfermedad por VRS. Como novedades de este año, se encuentran las siguientes: • Tabla de inmunizaciones sistemáticas para personas sanas y otra para pertenecientes a grupos de riesgo. • Aunque ya anteriormente se hacían recomendaciones de vacunación en embarazadas, se han añadido a la tabla y se ha creado un apartado específico. • Se recomienda la vacunación frente al neumococo con una de las nuevas vacunas conjugadas de valencia ampliada, en sustitución de VNC13. • Se recomienda la sustitución de la vacuna frente al meningococo C a los 4 meses de edad por la vacuna MenACWY, quedando la pauta recomendada como 1 + 1 + 1 (4 meses, 12 meses y 12 años, manteniendo el rescate en adolescentes hasta los 18 años). • Se recomienda la vacuna intranasal frente a gripe como la preferente en mayores de 2 años. • Siguiendo las propuestas de OMS, ECDC y CISNS, la vacunación frente al SARS-CoV-2 pasa a ser recomendada solo para personas mayores de 6 meses con factores de riesgo, con preparados que contengan el linaje XBB.1. Las recomendaciones de vacunación contra la covid en pediatría se actualizarán periódicamente en la web del CAV-AEP.Se mantienen el resto de las recomendaciones del calendario anterior.